2020
DOI: 10.22266/ijies2020.1231.18
|View full text |Cite
|
Sign up to set email alerts
|

Data Reduction for Optimizing Feature Selection in Modeling Intrusion Detection System

Abstract: With the development and ease of access to internet networks, the potential for attacks and intrusions have increased. The intrusion detection system (IDS), an approach to overcome this problem, is grouped into two models: signature-based and anomaly-based. An anomaly-based IDS can be implemented by machine learning; one of the schemes in machine learning is data reduction. IDS datasets are usually obtained through a real-time process that has undefined proportional data. The purpose of data reduction is to sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In the recent research trends, it has been observed that the method of feature selection is modified to boost the classification performance of the designed model. It has been found by [5], that, based on features selection and data reduction, the classification performance of the model enhances. The authors performed a test on three different sets of features to validate its hypothesis of enhancing the performance of a model on the basis of different features, and the performance of classification model became faster when the size of data was small.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In the recent research trends, it has been observed that the method of feature selection is modified to boost the classification performance of the designed model. It has been found by [5], that, based on features selection and data reduction, the classification performance of the model enhances. The authors performed a test on three different sets of features to validate its hypothesis of enhancing the performance of a model on the basis of different features, and the performance of classification model became faster when the size of data was small.…”
Section: Related Workmentioning
confidence: 99%
“…The Figure 3 represents the HNADAM-SDG flow chart, having a tendency to lower itself during convergence, and is represented using variable momentum and a step size, as in Equation ( 18) [5].…”
Section: Traditional Regression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The In the recent research trends it is been observed that the method of feature selection is modified to enhance the classification performance of the designed model. It has been found by (Iman and Ahmad, 2020) A hybrid approach has been introduced by (Pokuri., 2021) for analysing IDS using Naïve Bayes and improved BAT algorithm by analysing selected features. The author validates the hypothesis that the feature section methodology improves the performance of the anomaly detection model.…”
Section: Related Workmentioning
confidence: 99%
“…These amount and irrelevant feature problems in the dataset can be overcome by performing data preprocessing, such as feature selection [11][12][13] and data reduction [14][15][16]. Feature selection is used to remove unused features (x-dimensions) from the dataset, while data reduction is to remove unused data (ydimensions) from the dataset.…”
Section: Introductionmentioning
confidence: 99%